The best lanthanum tracing method of displaying kidney cell glycocalyxes with transmission electron microscope - LIU Zeng-bo; MEI Chang-lin; HU Hui-min; WANG Xue-qi; FU Li-li (Linchuang shenzangbing zazhi)
Objective The mice were infused with different schemes and kidney cell glycocalyxes were observed with transmission electron microscope.The aim was to find the best lanthanum tracing method of displaying kidney cell glycocalyxes.Methods C57/BL6 mice were divided into three groups according to infusion schemes.（1） Normal saline group:After venesection,the mice were infused through aorta with normal saline 5 ml.Then the kidneys were harvested and fixed with 2% lanthanum nitrate-glutaraldehyde fixative solution.（2） Lanthanum nitrate fixative group:The mice were infused with 2% lanthanum nitrate-glutaraldehyde fixative solution 5 ml and the kidney was fixed with the same fixative solution.（3） Lanthanum nitrate solution group:The mice were infused with 2% lanthanum nitrate solution 5 ml and 2% lanthanum nitrate-glutaraldehyde fixative solution 5 ml successively and the kidney tissues were fixed in the same way.The kidneys were processed to perform transmission electron microscope.The glycocalyxes of interstitial capillary endothelium,glomerular capillary endothelium,podocytes and interstitial cell junctions were observed.The glycocalyx displaying rates were calculated and compared.Results After tracing with lanthanum,the glycocalyxes of kidney cells were shown as electron-dense layers under transmission electron microscope.In the normal saline group,the glycocalyx displaying rates of interstitial capillary endothelium,glomerular capillary endothelium,podocytes and interstitial cell junctions were 0%,0%,20% and 92%,respectively.In the lanthanum nitrate fixative group,the glycocalyx displaying rates of the four different kidney cells were 16%,12%,84%and 96%,respectively.In the lanthanum nitrate solution group,the rates of kidney cells was 100%,96%,92% and 100%,respectively.The statistical results showed that the displaying rate of interstitial capillary endothelium and glomerular capillary endothelium was higher in lanthanum nitrate solution group or lanthanum nitrate fixative group than in normal saline group（P<0.01）.As compared with normal saline group,the displaying rate of lanthanum nitrate fixative group and lanthanum nitrate solution group was significantly increased（P<0.01）.There was no significant difference in glycocalyx displaying rate of interstitial cell junctions（F>0.05）.Conclusions The current study finds the best method of displaying kidney cell glycocalyxes:infusing mice with 2%lanthanum nitrate and 2% lanthanum-glutaraldehyde fixative solution successively,fixing kidney tissues with the same fixative solution and performing transmission electron microscope.This method can display different kinds of kidney cell glycocalyxes,especially kidney capillary endothelial glycocalyxes.The current study provides a reliable experimental method for the further studies related to kidney glycocalyx.